Pregão eletrônico: um estudo de caso desta ferramenta para aquisição de bens e serviços comuns - Feijó, Fábio Alexandre (2018)
The trading is a bidding modality regulated in 2002, by the law n. 10.520. In 2005, the decree 5.450 established an electronic form of trading that uses the technological resources of information. The present work is characterized as a descriptive research with a quantitative approach had as the goal to analyze the utilization of the Electronic Trading by UTFPR - Campus Londrina, as a tool to purchase common goods and services. For the achievement of this fundamental goal, were analyzed the physic processes of the Electronic Trading from years 2013, 2014, 2015 and 2016, to verify the priced values and the values actually paid at the end of the trading, in a way to fulfill the legal requirement of the economy of resources; it was verified the perception of the applicants related to the quality of the items acquired/hired. To ground the studies, were used works of consecrated authors that dealt with the theme of Public Administration, such as Bresser Pereira, Meirelles, Justen Filho, Bandeira de Mello, Di Pietro, Vareschini, Paludo, among others, and articles and studies from academicals that investigated the use of Electronic Trading in different institutions of the Brazilian Public Administration. The study concluded that, although on 1% of the items were acquired/hired by the value of the lowest estimate and 50% were awarded with a value higher than the one from the lowest estimate, the 49% acquired/hired by values lower than the ones from the lowest estimate rounded up to an economy of R$ 781.241,93, during the four studied years, based on the lowest estimates. About the quality of the items, it was verified that: 56% of the servers approved the quality of the goods and services acquired via Electronic Trading by UTFPR, as 44% showed some restrictions. For 45 of the answerers (86%), the products are the ones that show more quality problems; and for 31 (60%), the problems occur, mainly, in materials of consumption. To solve this problem, the researchers listed some suggestions, among them, the execution of feedback, and the presentation of samples from the offered products, the constant training of all the people involved in the process of the Electronic Trading, and a bank of data with information about the quality of the products of the companies that have already provided items to the university.